The Effect of Numbered Heads Together Cooperative Learning on the Collaborative Skills of Early Grade Students in Learning Multiplication - Halwa Tamara (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Collaborative skills are essential for early grade students as part of 21st-century competencies, yet they are often overlooked in traditional mathematics classrooms. This study aims to examine the effect of the Numbered Heads Together (NHT) cooperative learning model on the collaborative abilities of early grade students in learning basic multiplication. The research was driven by the low level of student engagement observed during conventional group work. A quantitative approach was used, employing a quasi-experimental design with a posttest-only control group. The participants consisted of 30 second-grade students at MIS Istiqomah, divided equally into experimental and control groups. The intervention was conducted over several sessions using structured NHT activities to enhance peer interaction and shared problem-solving. Data were gathered through a student-completed collaborative skills questionnaire and teacher observation sheets. Results indicated that the experimental group scored an average of 72.53 on collaboration measures, while the control group scored 39.07. An independent t-test revealed a significance value of 0.000 (p < 0.05), confirming a statistically significant difference. The findings demonstrate that the NHT model is effective in improving young learnersÔÇÖ collaboration during mathematics learning. Therefore, it can be recommended as a viable strategy to cultivate teamwork skills from an early stage of schooling.